2015
DOI: 10.1123/ijsnem.2014-0233
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Physiological Effects With Blackcurrant Intake in Endurance Athletes

Abstract: 19Blackcurrant contains anthocyanins, known to influence vasorelaxation and peripheral blood 20 flow. We examined the effects of 7 days intake of Sujon New Zealand blackcurrant powder 21 (6g/day) on the lactate curve, maximum oxygen uptake, and cardiovascular responses at rest and 22 during cycling. Thirteen trained triathletes with >3 yrs experience (8 men, age: 38±8 yrs, body 23As accepted for publication, http://journals.humankinetics.com/ijsnem As accepted for publication, http://journals.humankinetics.com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 7 publications
(9 reference statements)
1
79
2
Order By: Relevance
“…From the Fick equation [36], an increase in O 2 delivery (i.e., from an increase in cardiac output) would be expected to enable an increased uptake of O 2 . However, Willems et al [2] and Cook et al [4] did not observe any alteration in oxygen uptake during exercise following NZBC, therefore this warrants further investigation. In addition, the present study did not measure the pulmonary oxygen uptake response to the isometric contraction; therefore, this mechanism is speculative.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…From the Fick equation [36], an increase in O 2 delivery (i.e., from an increase in cardiac output) would be expected to enable an increased uptake of O 2 . However, Willems et al [2] and Cook et al [4] did not observe any alteration in oxygen uptake during exercise following NZBC, therefore this warrants further investigation. In addition, the present study did not measure the pulmonary oxygen uptake response to the isometric contraction; therefore, this mechanism is speculative.…”
Section: Discussionmentioning
confidence: 90%
“…Each capsule of 300 mg contains 105 mg of anthocyanins, i.e., 35%–50% delphinidin-3-rutinoside, 5%–20% delphinidin-3-glucoside, 30%–45% cyanidin-3-rutinoside, and 3%–10% cyanidin-3-glucoside with remaining content mainly natural plant sugars. The dose used was established from a previous study in which a dose-response relationship in cardiovascular responses was observed in trained cyclists [2]. Optimal dosing strategy for New Zealand blackcurrant extract is not known.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ammar et al [131] showed that pomegranate juice lowered the perception of knee extensor soreness and attenuated the acute rise in specific markers of tissue damage [e.g., creatine kinase (CK), lactate dehydrogenase] 3 min after Olympic weight-lifting movements, and improved the recovery kinetics of these same markers 48 h after exercise. Blackcurrant has been studied for its effects on exercise performance [135, 136], substrate oxidation [137], and physiological measures, such as blood lactate level [135, 136, 138]. Only one study has tested the effects of BC on exercise-induced muscle damage, subjective ratings of muscle soreness, and inflammation post-exercise [133].…”
Section: Micronutrientsmentioning
confidence: 99%